2022
DOI: 10.3390/microorganisms10071405
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Microbiota, Olfactory Health, Neurological Disorders and Aging—A Review

Abstract: The nasal region is one of the distinct environments for the survival of various microbiota. The human microbial niche begins to inhabit the human body right from birth, and the microbiota survive as commensals or opportunistic pathogens throughout the life of humans in their bodies in various habitats. These microbial communities help to maintain a healthy microenvironment by preventing the attack of pathogens and being involved in immune regulation. Any dysbiosis of microbiota residing in the mucosal surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 195 publications
0
20
0
4
Order By: Relevance
“…The investigation was prompted by the proximity of facial bones to the nasal passages and sinuses, housing the nasal microbiota crucial for immune regulation and general CNS homeostasis. 52,53 The TSPO signal in facial bones may be sensitive to changes in these spaces; however, further research is needed to elucidate the connection between facial bones and nasal passages and its implications for the brain-periphery connection.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation was prompted by the proximity of facial bones to the nasal passages and sinuses, housing the nasal microbiota crucial for immune regulation and general CNS homeostasis. 52,53 The TSPO signal in facial bones may be sensitive to changes in these spaces; however, further research is needed to elucidate the connection between facial bones and nasal passages and its implications for the brain-periphery connection.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies suggested that the nasal microbiota has been significantly associated with the central nervous system and immune system. Dysbiosis in the nasal microbiota may lead to inflammatory diseases and pathological invasion of the nasal cavity, which may damage the olfactory system [ 34 ].…”
Section: Air Pollution Impact On Nasal Microbiotamentioning
confidence: 99%
“…The microbes, like a Trojan-horse, cross the BBB either transcellularly or paracellularly or with the help of infected phagocytes. Then, the presence of these elements alters the BBB function causing increased permeability, encephalopathy, or pleocytosis [4].…”
Section: ) the Trigeminal Routementioning
confidence: 99%
“…The role of nasal microbiota has been investigated in neurodegenerative diseases such as Parkinson's Disease (PD) [1]; however, neither Pereira [2] nor Heintz-Buschart [3] identified any differences in the nasal microbiota composition comparing PD patients and healthy controls. Thangaleela in 2022 speculated that metabolites from nasal microbiota could pass through the Blood Brain Barrier (BBB) [4]. If this hypothesis could be confirmed, the effect of nasal microbiota in the development of neuro-inflammation and neurodegeneration could be like that of gut microbiota [1,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation